Meningkatkan Keterampilan Gerakan Sholat Pada Siswa Tunagrahita Ringan Melalui Media Vidio Tutorial di Kelas III SLB Negeri Madina - Fatiah, Siti; Ardisal, Ardisal (Jurnal Penelitian Pendidikan Khusus, 2022)
This research is motivated by the ability of prayer movement skills, mild mentally retarded students who are in SLB Negeri Madinawhich offect their prayer ability. This students aims to improve the prayer movement skills of mild mentally reterded. This research is a classroom action research with a quantitative approach with percentage and qualitative descriptipe analysis consisting of four stages, namely planning, observing and reflecting. This study consisted of to acls with on acclus consisting of four meeting where 3 action meetings were carried out and one test meeting. Subick in this study amounted to two mild mentally reterdet students who were in class III. The data collection technique in this study used a prayer movement skill test, interview, observation and documentation. Instrument validation was carried out by supervisors and teachers of Islamic religious subject class III SLB Madian. Data analysis was carried out descriptively quantitatively and qualitatively with persentages. The results showed that the use of vidio tutorial can improve prayer movements skills in mild mentally retardate students in class III SLB Negeri Madina, this is evidenced by an increase in the ability of prayer movement skills, namely, subject A from the ability of the initial ability 53,33% experienced an increase of 11,67% to 65% in the first cycle and an increase of 20% to 85%  in the cycle, then the total increase  achieved by subject A was 31,67%. Subject B and the initial ability of 58,33% increased by 5,83% to 64,16% in the firs cycle and increased by 19,17% to 83,33% in the second cycle, then the totalincrease achievedby subject B is 25%. And daring the process to achiee the goal, preparation, conditioning for improvement  as well as motivation and reward are carried out.